Аbout Yugoslavia on the Eve of Its Establishment: Nikola Pašić and British Prime Minister David Lloyd George About the Future Yugoslav State on 15th October 1918 - Sovilj, Milan P. (Sociološki pregled, 2019)
The study reviews the meeting of President of the Serbian Government Nikola Pašić and British Prime Minister David Lloyd George in London on 15th October 1918. On that occasion the two statesmen expressed their respective attitudes about the situation in the territory where the establishment of the Yugoslav state was anticipated. It could be clearly derived from Pašić’s attitudes that the decisive role in the process of the unifcation of Serbs, Croats and Slovenes should be played by Serbia. However, Lloyd George emphasized another signifcant moment of the future unifcation – the attitude of the Yugoslav population in the territory of Austria-Hungary. Complex political events and the process of the breakup of Austria-Hungary did not leave much space either for the realization of Nikola Pašić’s aspirations or the emphasis of the attitude of the local population referred to by Lloyd George.